Актуальні питання медико-психологічної реабілітації посттравматичного стресового розладу = Issues of medical and psychological rehabilitation post traumatic stress disorder - Puzanova, A.; Gozhenko, E.; Yanchuk, O.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Puzanova A., Gozhenko E., Yanchuk O., Zukow W. Актуальні питання медико-психологічної реабілітації посттравматичного стресового розладу = Issues of medical and psychological rehabilitation post traumatic stress disorder. Journal of Education, Health and Sport. 2015;5(9):273-282. ISSN 2391-8306. DOI10.5281/zenodo.30628 http://dx.doi.org/10.5281/zenodo.30628 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A273-282 https://pbn.nauka.gov.pl/works/621538 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 06.09.2015. АКТУАЛЬНІ ПИТАННЯ МЕДИКО-ПСИХОЛОГІЧНОЇ РЕАБІЛІТАЦІЇ ПОСТТРАВМАТИЧНОГО СТРЕСОВОГО РОЗЛАДУ ISSUES OF MEDICAL AND PSYCHOLOGICAL REHABILITATION POST TRAUMATIC STRESS DISORDER Пузанова А.Г., Гоженко О.А., Янчук А.А., Zukow W. Puzanova A.G., Gozhenko Elena, Yanchuk Oleksandr, Zukow W. ДП «Український НДІ медицини транспорту МОЗ України» Миколаївський політехнічний університет Uniwersytet Kazimierza Wielkiego w Bydgoszczy Ключові слова: медико-психологічна реабілітація; посттравматичний стресовий розлад. Key words: medico-psychological rehabilitation; post traumatic stress disorder. Резюме В статье представлены современные представления о причинах формирования посттравматического стрессового расстройства. Описаны особенности проявления стрессорного расстройства у военнослужащих (солдат) и медицинского персонала. Рассмотрены подходы к обследованию и немедикаментозного лечения пациентов. Особое внимание уделено возможностям посстрессовой реабилитации и ее современным методикам, а именно вариантам психотерапии, кинезотерапии, бальнеотерапии, физиотерапии. Summary This article presents modern views on the causes of formation of post-traumatic stress disorder. Describes the features of the manifestations of stress disorders among troops (soldiers) and medical personnel. Approaches to survey and non-medical treatment of patients. Special attention is given to the possibilities of rehabilitation poststress and its modern methods, namely psychotherapy options, kinesitherapy, balneotherapy, physiotherapy.